Determination of Some Soil Characteristics of Roadside Landslides Region: A Case Study of Lapseki-Sevketiye (Canakkale) - Mehmet Parlak (Doğal Afetler ve Çevre Dergisi)
Landslides bring about serious environmental problems. Roadside landslides are a common natural phenomenon. They are often triggered by a combination of steep relief, rainfall and soil properties. The loss of upper fertile soil layer is among the most significant environmental problems induced by landslides. Such losses lead to land degradation. This study was conducted to compare some characteristics (pH, electrical conductivity, lime, organic matter, total nitrogen (N), available phosphorus (P), available potassium (K), texture, aggregate stability, liquid limit, plastic limit, plasticity index, and clay activity) of the soils (0-10 cm depth) taken from inside and wheat field of a landslide occurred at the side of Canakkale-Bursa highway (around Sevketiye section). In comparison of soil properties the paired t test was used. While wheat field samples had higher electrical conductivity, organic matter, available potassium (K), clay, silt, and plasticity index, but lower pH and fine sand contents than the inside samples. Statistically significant differences were not observed in terms of lime, total nitrogen (N), available phosphorus (P), available potassium (K), coarse sand, liquid limit, plastic limit, plasticity index and clay activity. Farmyard manure, harvest residues or compost can be applied to improve soil characteristics in landslide-influenced areas.